2019
DOI: 10.1186/s40824-018-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

3D printable hyaluronic acid-based hydrogel for its potential application as a bioink in tissue engineering

Abstract: BackgroundAfter recognition of 3D printing and injectable hydrogel as a critical issue in tissue/organ engineering and regenerative medicine society, many hydrogels as bioinks have been developed worldwide by using polymeric biomaterials such as gelatin, alginate, hyaluronic acid and others. Even though some gels have shown good performances in 3D bioprinting, still their performances do not meet the requirements enough to be used as a bioink in tissue engineering.MethodIn this study, a hydrogel consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(110 citation statements)
references
References 39 publications
2
101
0
2
Order By: Relevance
“…Currently, several studies have used HA or HA derivatives as bioinks for the fabrication of tissue-engineered bone constructs. Noh et al synthesized a hybrid hydrogel from HA, hydroxyethyl acrylate (HEA), and gelatin-methacryloyl and used it as a cell-laden bioink for bone regeneration [109]. The results demonstrated that the hybrid hydrogel showed excellent biocompatibility and good printability (Figure 7a).…”
Section: D Printing Fabrication Of Porous Scaffoldsmentioning
confidence: 99%
“…Currently, several studies have used HA or HA derivatives as bioinks for the fabrication of tissue-engineered bone constructs. Noh et al synthesized a hybrid hydrogel from HA, hydroxyethyl acrylate (HEA), and gelatin-methacryloyl and used it as a cell-laden bioink for bone regeneration [109]. The results demonstrated that the hybrid hydrogel showed excellent biocompatibility and good printability (Figure 7a).…”
Section: D Printing Fabrication Of Porous Scaffoldsmentioning
confidence: 99%
“…Both natural and synthetic polymers are applicable in preparing hydrogelsbased bio-inks. [86][87][88] Although synthetic polymers, including pluronic 89 and PEG, 66 have shown an impressive mechanical strength, often natural polymers, that is, collagen, fibrin, 90 hyaluronic acid, 91 alginate, 92 chitosan, 93 and so forth, are preferred due to the inherent bioactivity or better simulation of natural ECM. 94,95 Also, some of the natural polymers with signaling molecules can promote cellular processes while the living organism-derived polymers are not suitable in cellular interactions.…”
Section: Scaffold-based Bio-inksmentioning
confidence: 99%
“…For extrusion based printing, hyaluronic acid has been grafted with hydroxyethyl acetate and gelatin-methacrylate to form a hydrogel which was 3D printed into a scaffold with~500 µm resolution [210]. One way to tune mechanical robustness and macro-porosity beyond that of hydrogels is to formulate hyaluronic acid cryogels (hydrogels produced through controlled freezing and thawing of a polymer solution), which have also been 3D printed [211].…”
Section: Structural and Mechanical Propertiesmentioning
confidence: 99%
“…Hyaluronic acid and modified hyaluronic acid show good cyto-and bio-compatibility [207,210], as it is naturally a part of the extra-cellular matrix. Extruded hyaluronic acid structures show excellent bioactivity, with hyaluronic acid based hydrogel scaffolds for improving cell viability [208], promotion of stromal cell elongation with applications in building liver models for drug screening [209], retinal cells culturing [216], immobilization of peptides for mesenchymal stem cell culturing with high angiogenic and osteogenic activity [217], deposition of regenerative scaffolds directly during surgery [218], and supporting human adipose progenitor cell and stromal cell adhesion and proliferation [211].…”
Section: Biocompatibility Biodegradability and Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation